Partial Ectopia Cordis: A Case Report - Reza Saeidi; Ashraf Mohammadzadeh; Ahmadshah Farhat; Mohammadreza Naghibi; Hassan Birjandi; Saeedreza Lotfi (Mashhad University of Medical Sciences, 2017)
Background: One-third of all major congenital anomalies are Congenital heart disease (CHD) and Reported CHD prevalence increased over time and in Asian countries is more than western countries. Ectopia cordis (EC) is a rare congenital anomaly with an estimated incidence of 1:100 000 live births in developed countries. EC is characterized by abnormal heart placement outside the thorax, mostly on the thoracoabdominal side. This form is often associated with pentalogy of Cantrell.Case report: We report one cases of the ectopia cordis at the Emam Reza Hospital in Mashhad. In this report, a rare case with incomplete pentalogy of Cantrell are described. It was a boy with a large omphalocele with evisceration of the heart. He had normal capillary refill and responded to stimuli. This patient was a male fetus with ectopia cordis with intracardiac anomalies; a large omphalocele with evisceration of the heart; a hypoplastic sternum and rib cage.Conclusion: Prognosis seems to be poorer in patients with the complete form of pentalogy of Cantrell, EC, and patients with associated anomalies. Intracardial defects do not seem to be a prognostic factor